VERB TRANSLATIONS IN PUBLIC SIGNS FROM JAKARTA’S INTEGRATED TRANSPORTATION - Ina Sukaesih (LinguAmerta, 2024)
The translation of public signs is classified as an inter-language translation because it involves two languages: Indonesian as the source language and English as the target language. On the other hand, the differences in grammatical rules sometimes cause a translation shift. In the case of public signs, people have noticed some ineffective sentences and unnatural translations provided in public transportation that should be improved by the stakeholder. This study focuses on the English-translated public sign and intends to indicate the function of public sign, translation technique, and types of verb shift. Moreover, the verb translation in public signs is analyzed to figure out how verb translation affects the accuracy and acceptability of the whole sentence. Content analysis and Focus Group Discussion (FGD) were used to collect the data. Qualified raters conducted FGD to assess the accuracy and acceptability aspects. Data was collected from public signs in Jakarta’s integrated transportation, such as Transjakarta, MRT Jakarta, LRT Jakarta, and KAI Commuter. Findings reveal that verb translations in public signs from Jakarta’s integrated transportation mostly produce a translation shift and have a lower score in terms of accuracy and acceptability. The quality is considered “less accurate and acceptable” with an average score of 2.12 due to distortions of meaning, grammatical errors, and improper collocations. In addition, some data used unnatural or uncommon terms for the English reader. Keywords: Integrated Transportation; Public Sign Translation; Translation Quality; Translation Shift; Translation Technique.